Habitus Santri Ramah Lingkungan: Etnografi Pembentukan Kesadaran Ekologis melalui Disiplin Spiritual di Pesantren Hidayatul Mubtadiin - Moh. Mahfud (Pascasarjana IAI Al-Khairat Pamekasan, 2025)
This study aims to analyze the process of forming environmentally friendly santri (Islamic boarding school students) habits through spiritual discipline at Pesantren Hidayatul Mubtadiin in Pamekasan. Using a qualitative ethnographic approach with participant observation, in-depth interviews, and document study techniques, this research reveals that ecological awareness is built through the organic integration of Sufi practices (riyadhah) and daily actions. The findings indicate that rituals such as congregational prayer, dhikr (remembrance of God), fasting, and ascetic practices (tirakat) function as vehicles for value internalization, constructing nature as a manifestation of God's signs that must be preserved. These values are then incorporated through the repetition of bodily actions, giving rise to automatic practical habits in waste management, water conservation, and organic farming. Ecological awareness is not taught separately but is woven into a web of meaning connecting environmental jurisprudence (such as the prohibition of israf/wastefulness), Sufi ethics (heart purification), and narratives of tawhid (divine unity) regarding the oneness of creation. This study concludes by proposing the